Gestão de estoques no ramo varejista de supermercados : um estudo de caso sobre o supermercado XYZ - Machado, Marcos Vinícius (2022)
The present study aimed to discuss Inventory Management as a source of improvements for the results of a supermarket retailer. Thus, concepts and methods relevant to the proposed theme were presented in their theoretical foundation. Therefore, the present work was carried out through the methodology of the case study, being approached through a structured questionnaire, as well as through field visit and documental analysis. Based on the data collected, we sought to verify the company's internal processes in view of the concepts presented in its theoretical foundation, and thus, carry out a pertinent analysis of the proposed theme. In view of the above, it was possible to verify the lack of internal controls related to Inventory Management in the company, partly due to the lack of knowledge of its managers regarding the benefits that can be obtained, and others, due to resistance to internal changes and the lack of objectives regarding the maintenance and expansion of its business, due to the stability that the company has over time in its business, in the branch in which it operates in its locality. Therefore, we sought to elucidate the company about the importance of Inventory Control and its management, as well as the benefits that they may obtain in relation to its business and internal processes with its implementation. It was also sought, through the analyzes carried out, to identify possible improvements regarding the internal processes currently carried out, presenting them through suggestions and recommendations.